Portable marketing set - Mohamad Sa’ad, Mohamad Syahid; Hassan, Mohd Fahrul; Junairi, Mohamad Hasrul; Kamaruzaman, Mohamad Ridzuan; Ismail, Mohamad Rizal (Penerbit UTHM, 2017)
Folding table (Figure 8.1) that consist of chair or also known as “Portable Table” is an item that have been widely used all over the world. However, in Malaysia this concept of idea is still new and needs publicities. This portable table usually consist of a rectangular table and chairs around it. The development of the table is based from the dining table at home to gather family member and for eating. Folding tables are produced in many sizes, design and configuration and it can be made from plastic, metal, plastic and other material. Mostly special material will be used by engineer to produces the product.